Histamine and Histamine H4 Receptor Promotes Osteoclastogenesis in Rheumatoid Arthritis - Kyoung-Woon Kim (Nature Portfolio, 2017)
Abstract Histamine H4 receptor (H4R) has immune-modulatory and chemotaxic effects in various immune cells. This study aimed to determine the osteoclastogenic role of H4R in rheumatoid arthritis (RA). The concentration of histamine in synovial fluid (SF) and sera in patients with RA was measured using ELISA. After RA SF and peripheral blood (PB) CD14+ monocytes were treated with histamine, IL-17, IL-21 and IL-22, and a H4R antagonist (JNJ7777120), the gene expression H4R and RANKL was determined by real-time PCR. Osteoclastogenesis was assessed by counting TRAP–positive multinucleated cells in PB CD14+ monocytes cultured with histamine, Th17 cytokines and JNJ7777120. SF and serum concentration of histamine was higher in RA, compared with osteoarthritis and healthy controls. The expression of H4R was increased in PB monocytes in RA patients. Histamine, IL-6, IL-17, IL-21 and IL-22 induced the expression of H4R in monocytes. Histamine, IL-17, and IL-22 stimulated RANKL expression in RA monocytes and JNJ7777120 reduced the RANKL expression. Histamine and Th17 cytokines induced the osteoclast differentiation from monocytes and JNJ7777120 decreased the osteoclastogenesis. H4R mediates RANKL expression and osteoclast differentiation induced by histamine and Th17 cytokines. The blockage of H4R could be a new therapeutic modality for prevention of bone destruction in RA.